(untitled) (Baghdad Science Journal, 2014)
The corrosion behavior of low carbon steel in washing water of crude oil solution has been studied potentiostatically at five temperatures in the range (30–70)°C .The corrosion potential shifted to more negative values with increasing temperature and the corrosion current density increased with increasing temperature. Folic acid had on inhibiting effect on the corrosion of low carbon steel in washing water at a concentration (5× 10-4– 5× 10-3 ) mol/dm3 over the temperature range (30–70)°C. Values of the protection efficiency were calculated from the corrosion current density .From the general results for this study, it can be seen that thermodynamic and kinetic function were also calculated (?G, ?S, ?H and Ea ) to comparison these values in presence and absence of inhibitor (folic acid ).